2020
DOI: 10.3390/ijms21114017
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between Thioacetamide-Induced Liver Injury in Rat and Human In Vitro Gene Expression Data

Abstract: The immense resources required and the ethical concerns for animal-based toxicological studies have driven the development of in vitro and in silico approaches. Recently, we validated our approach in which the expression of a set of genes is uniquely associated with an organ-injury phenotype (injury module), by using thioacetamide, a known liver toxicant. Here, we sought to explore whether RNA-seq data obtained from human cells (in vitro) treated with thioacetamide-S-oxide (a toxic intermediate metabolite) wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…To further corroborate the relevance of cSL load to carcinogenesis, we next investigated whether carcinogen treatment in normal (noncancer) cell lines and primary cells in vitro can lead to cSL load decrease. First, we analyzed gene expression data from a recent study where human primary hepatocytes, renal tube epithelial cells, and cardiomyocytes were treated with the carcinogen and hepatotoxin thioacetamide- S -oxide ( 25 ). We computed the cSL load in each cell type after treatment versus control and found a significant decrease of cSL load only in the hepatocytes (Wilcoxon rank sum test P = 0.014; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further corroborate the relevance of cSL load to carcinogenesis, we next investigated whether carcinogen treatment in normal (noncancer) cell lines and primary cells in vitro can lead to cSL load decrease. First, we analyzed gene expression data from a recent study where human primary hepatocytes, renal tube epithelial cells, and cardiomyocytes were treated with the carcinogen and hepatotoxin thioacetamide- S -oxide ( 25 ). We computed the cSL load in each cell type after treatment versus control and found a significant decrease of cSL load only in the hepatocytes (Wilcoxon rank sum test P = 0.014; Fig.…”
Section: Resultsmentioning
confidence: 99%
“… ( A ) Box plots showing the cSL loads in control versus thioacetamide- S -oxide–treated samples in human primary hepatocytes (“liver”), renal tube epithelial cells (“kidney”), and cardiomyocytes (“heart”), using the data from ( 25 ). One-sided Wilcoxon rank-sum test P values are shown.…”
Section: Resultsmentioning
confidence: 99%
“…For a biological interpretation, we categorized the histological endpoint into their pathological responses, inflammation, degeneration, and proliferation. The gene module approach outperforms individual genes in predicting severity of histological damage ( AbdulHameed et al, 2014 ; Tawa et al, 2014 ; Te et al, 2016 ; Schyman et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…However, they do not offer detail mechanistic insights, which KEGG pathways or wiki-pathways can provide ( Kanehisa and Goto, 2000 ; Martens et al, 2020 ). We have shown that the combination of our modular approach to identify key injury phenotype together with pathway analysis, provided in ToxPanel, can be useful when understanding the underlying molecular mechanisms in e.g., liver or kidney injury ( Schyman et al, 2020a ; Schyman et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation